(untitled) (Al-Academy, 2023)
The current specialized research tagged (intellectual and artistic concepts of the cultural context and their impact on contemporary ceramic sculpture) paves the way for the emergence of the context in ceramics active in life, so that this relationship will indicate the development and presence of ceramics or not and the volume of its circulation in the joints of the culture of the Arab recipient. As a result, the researcher collected scientific materials to serve the subject of the research in four chapters: Chapter One (General Methodological Framework) To clarify the problem of the research, the importance of the research to achieve benefit in higher education and education for scholars and teachers, while the research aims to reveal the development of cultural contexts and their impact on the production and circulation of contemporary Arab ceramic art. They are the Arab countries, then the search terms were identified and defined. As for the second chapter (theoretical framework), it included three axes: the first: meaning Context. The second axis: thinkers’ views of the context in language and linguistics. The third axis: the emergence of the context as representations in the artistic form, and in the third chapter (research procedures) the researcher reviewed the presence of ceramics in the Arab reality through the analysis of ceramic sculptural patterns. The researcher aims to select a sample that represents the boundaries of the research, its aim, and the framework of society. - Research tool: In order to achieve the goal of the research and to identify (the intellectual and artistic concepts of the cultural context and their impact on contemporary ceramic sculpture The researcher adopted the indicators concluded by the theoretical framework, and the researcher concluded in the fourth chapter a number of results: 1- The Arab audience formed a presence represented in the demand for works with peripheral contents in favor of types of cultural and artistic reception in addition to the factional and media. 2- Formal behavior in art. The contemporary Arab, the Arab recipient voluntarily accepts the forms within the ceramic sculptural work and its abbreviations brought by the postmodern culture other than what we have seen, as it simulates the forms through their symbols and meanings on the one hand and preserves their contents on the other hand. In addition to the conclusions, recommendations and proposals.